Energy‐efficient interference management in LTE‐D2D communication. Issue 3 (1st May 2016) - Mumtaz, Shahid; Saidul Huq, Kazi Mohammed; Rodriguez, Jonathan; Frascolla, Valerio
Abstract : This paper focuses on one of the key enabling technology that will compose future 5G network, the Direct‐LTE communication underlying a cellular infrastructure, also commonly known as Device‐to‐Device (D2D). Energy efficiency algorithms are proposed for the communication between D2D users and cellular users (CUs) and, following the Lagrangian duality theory, an optimal power and rate control solution is given for D2D users, while satisfying the interference limits related to CUs. Finally, the new algorithm is used to achieve proportional fairness between D2D users and CUs and to show with numerical results that the interference to CUs can be limited to always be under a predefined threshold.